Understandability of passive smoking prevention leaflets in Japan - Iso, Tomoya; Ishikawa, Yoshihiro; Kobashi, Yurie; Nollet, Kenneth; Yokokawa, Hirohide; Goto, Aya (Frontiers in Communication, 2024)
There are few studies in Japan evaluating informational materials about passive smoking prevention with respect to health literacy. This study applied a range of health literacy assessment tools to assess the understandability of public-sector leaflets about passive smoking prevention.We collected 26 anti-passive smoking leaflets published online by Japanese prefectural governments. We used three internationally recognized health literacy assessment tools to evaluate their understandability: the Clear Communication Index (CCI), the Suitability Assessment of Materials (SAM), and the Patient Education Materials Assessment Tool (PEMAT, further divided into scales for understandability and actionability).Results: Although none of the assessed materials met the CCI's scoring threshold for "easy to understand," the highest-scoring leaflet, which received a top-two ranking in three of the four scales (excluding the PEMAT understandability scale), was characterized by its conciseness and its easy-to-understand structure, including the use of checklists and flowcharts to engage reader interest. There was a significant correlation between CCI and SAM, and between SAM and the PEMAT understandability scale. However, the PEMAT actionability scale did not significantly associate with the other assessment scales.The understandability of written informational materials about passive smoking prevention in Japan could be improved by referring to multiple assessment scales.